Service Quality of Government Institution and Its Influence on Public Satisfaction (Study in Regency/City Government of North Sulawesi) - Hendrik Gamaliel; Lintje Kalangi; Jessy Warongan (AIBPM Publisher, 2022)
This study aims to empirically examine the influences of the service quality of government institutions on public satisfaction and the degree of influences of service quality among regencies/cities in the North Sulawesi Province. This study focuses on the performance measurement of One-Stop Integrated Service and Investment Service. Respondents of this research are a community in four regencies/cities in the province of North Sulawesi that is Manado City, Bitung City, Bolaang Mongondow Regency, and Kotamobagu City. The respondents are those who have experienced the services provided by One-Stop Integrated Service and Investment Service institutions in those regencies/cities. This study uses a survey method that distributes questionnaires to each region. The data analysis method uses multiple linear regression analyses. The results show that of the 6 (six) hypotheses, 5 (five) hypotheses were supported and 1 (one) hypothesis was not supported. Supported hypotheses are 1, 2, 3, 4, and 5 hypotheses. Meanwhile, the 6 hypotheses are not supported.